Bates' Visual Guide to Physical Examination: A Review. Issue 4 (2nd October 2022) - Whitney, Rachel
Abstract: Bates Visual Guide to Physical Examination is a web-based companion to the text B ates' Guide to Physical Examination and History Taking by Lynn Bickley, MD. This site contains other multimedia features including video and audio. It is designed for students and faculty in medical, nursing, and related programs and provides head-to-toe and systems-based physical examination techniques. This review will assess its content, navigation, and search functions, and describe its special features.